PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN PADA RESTORAN CEPAT SAJI LOKAL DI KOTA BANDUNG - Muzaffirah, Adzirah; Abdul Wahib Muahimin; Kliwon Hidayat (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2026)
The food and beverage industry experienced significant growth globally, including in Indonesia, as evidenced by the increasing number of fast-food restaurants. Bandung City emerged as a hub for the culinary industry's development, particularly local fast-food restaurants competing with international brands. However, intense competition required local fast-food restaurants to optimize their marketing strategies to enhance customer satisfaction and loyalty. This study identified the influence of the marketing mix (7P) and local brand awareness on customer satisfaction and loyalty in local fast-food restaurants in Bandung City. Using a quantitative approach with the SEM-PLS method, the study involved 203 respondents who met specific criteria. The findings indicated that the marketing mix and local brand awareness significantly impacted customer satisfaction and consumer loyalty. These results provided critical contributions for local fast-food restaurant businesses to improve their competitiveness through effective marketing strategy implementation.